Petrobactin Is Exported from Bacillus anthracis by the RND-Type Exporter ApeX - A. K. Hagan; A. Tripathi; D. Berger; D. H. Sherman; P. C. Hanna (mBio, 2017)
ABSTRACT Bacillus anthracis—a Gram-positive, spore-forming bacterium—causes anthrax, a highly lethal disease with high bacteremia titers. Such rapid growth requires ample access to nutrients, including iron. However, access to this critical metal is heavily restricted in mammals, which requires B. anthracis to employ petrobactin, an iron-scavenging small molecule known as a siderophore. Petrobactin biosynthesis is mediated by asb gene products, and import of the iron-bound (holo)-siderophore into the bacterium has been well studied. In contrast, little is known about the mechanism of petrobactin export following its production in B. anthracis cells. Using a combination of bioinformatics data, gene deletions, and laser ablation electrospray ionization mass spectrometry (LAESI-MS), we identified a resistance-nodulation-cell division (RND)-type transporter, termed ApeX, as a putative petrobactin exporter. Deletion of apeX abrogated export of intact petrobactin, which accumulated inside the cell. However, growth of ΔapeX mutants in iron-depleted medium was not affected, and virulence in mice was not attenuated. Instead, petrobactin components were determined to be exported through a different protein, which enables iron transport sufficient for growth, albeit with a slightly lower affinity for iron. This is the first report to identify a functional siderophore exporter in B. anthracis and the in vivo functionality of siderophore components. Moreover, this is the first application of LAESI-MS to sample a virulence factor/metabolite directly from bacterial culture media and cell pellets of a human pathogen. IMPORTANCE Bacillus anthracis requires iron for growth and employs the siderophore petrobactin to scavenge this trace metal during infections. While we understand much about petrobactin biosynthesis and ferric petrobactin import, how apo-petrobactin (iron free) is exported remains unknown. This study used a combination of bioinformatics, genetics, and mass spectrometry to identify the petrobactin exporter. After screening 17 mutants with mutations of candidate exporter genes, we identified the apo-petrobactin exporter (termed ApeX) as a member of the resistance-nodulation-cell division (RND) family of transporters. In the absence of ApeX, petrobactin accumulates inside the cell while continuing to export petrobactin components that are capable of transporting iron. Thus, the loss of ApeX does not affect the ability of B. anthracis to cause disease in mice. This has implications for treatment strategies designed to target and control pathogenicity of B. anthracis in humans.